If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -2) = (4x + 3) Reorder the terms: (-2 + 7x) = (4x + 3) Remove parenthesis around (-2 + 7x) -2 + 7x = (4x + 3) Reorder the terms: -2 + 7x = (3 + 4x) Remove parenthesis around (3 + 4x) -2 + 7x = 3 + 4x Solving -2 + 7x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 7x + -4x = 3 + 4x + -4x Combine like terms: 7x + -4x = 3x -2 + 3x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + 3x = 3 + 0 -2 + 3x = 3 Add '2' to each side of the equation. -2 + 2 + 3x = 3 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 3 + 2 3x = 3 + 2 Combine like terms: 3 + 2 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| 9(z+6)=4(z-4) | | 40=(2x+3)(x+7) | | z^2+2z=c | | 3x-1=-34 | | 8x-6y+1=13 | | X(5x-4)=6 | | (X-5)(x^2-3x+2)=0 | | 5.4-6m=-6 | | 5k-6+k=3(4k-6) | | 7x/5x=1/5 | | D=5yards | | r-75=3.1 | | 3.14xsquared=314 | | 3(4+5s)-12+(-3s)= | | 2x+12=7x-13 | | 7y-4x=9 | | 5x^2-12x+1=-6 | | 10x-2x-12= | | 64t^3-25t=0 | | -1x-52=42 | | -4/7n=-8 | | x/-2=-20 | | 8/9-3/9= | | x+6=-12x+6 | | 2x(10)=6x^2 | | 18+y-9=60 | | 3v^2+6v-240= | | -6x+12y=-18 | | 7(r+2)=35 | | 2d+7=3d | | 8x-3=12+2x | | 24=2(y+6) |